2023
DOI: 10.3389/fsufs.2023.1137683
|View full text |Cite
|
Sign up to set email alerts
|

Farm2Fork through the lens of community ecology: concepts and applications in postharvest storage

Abstract: The environment in which postharvest crops are processed and stored is a dynamic ecosystem influenced not only by environmental factors such as temperature and humidity, but also by biotic influences such as humans and insects. Abiotic influences such as variation in landscapes of warehouses, processing facilities, storage and shipping containers, and urban and agricultural settings can also drive changes in ecosystem processes for insects living in a postharvest system. Principles of community ecology can hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 201 publications
0
2
0
Order By: Relevance
“…The direct effects of evolutionary history, behaviour and physiology on the ecology and species biological responses to rising global temperatures are increasingly being documented [137,147,148]. Environmental conditions can alter the form, function and behaviour of organisms through physiological responses over short and long timescales and even over generations [149,150].…”
Section: Climate Change and Environmental Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct effects of evolutionary history, behaviour and physiology on the ecology and species biological responses to rising global temperatures are increasingly being documented [137,147,148]. Environmental conditions can alter the form, function and behaviour of organisms through physiological responses over short and long timescales and even over generations [149,150].…”
Section: Climate Change and Environmental Attributesmentioning
confidence: 99%
“…Some successful non-indigenous species are more tolerant to environmental and anthropogenic stressors than related native species, possibly stemming from evolutionary selection pressure (i.e., survival of only pre-adapted individuals for particular environmental conditions) during the invasion process [ 135 ]. Owing to this is the notion that invasive alien species are more eurythermal, i.e., able to maintain physiological functionality across variable temperatures [ 136 , 137 ]. Rapid adaptation is recognised as an important component of successful invasions [ 138 ].…”
Section: Biological Invasions: Donors Drivers and Processes Involvedmentioning
confidence: 99%
“…Hubert et al (2021) found that microbes are commonly found in the diet of dust mites; the bacterial genera Bacillus, Staphylococcus, and Kocuria were found in the diet where house dust mites had fed and microbe composition differed depending on the presence of mite life stages, including eggs and mite bodies. The microbial community can be influenced by the ecological succession of stored product insects (and vice versa) (Fandohan et al, 2003;Gerken & Morrison, 2023). Primary or internal-infesting insect pest will bring their own microbial colonizers to undamaged kernels that may be separate from secondary or external-infesting pests that can take advantage of damaged kernels and grain dust.…”
Section: Introductionmentioning
confidence: 99%